Implementation of Religious Character Building at Ma’had Al-Jami’ah UIN Palangka Raya - Dandi Ardiansyah; Zainap Hartati; Neela Afifah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to analyse the implementation of religious character development for student residents at Ma’had Al-Jami’ah UIN Palangka Raya through structured religious programs and boarding-based activities. This research employed a qualitative case study approach involving 12 informants consisting of Ma’had administrators, musyrif/musyrifah, ustadz/ustadzah, and students. Data were collected through observation, interviews, and documentation, then analysed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that religious character development is implemented through congregational prayers, Quran recitation, Islamic studies, worship habituation, discipline monitoring, and role modelling by mentors. These activities foster character values such as discipline, responsibility, honesty, politeness, social awareness, and devotion to worship. The internalization process is strengthened through continuous habituation, intensive social interaction, and a conducive religious environment within the ma’had. Supporting factors include structured mentoring programs and active mentor involvement, while inhibiting factors include students’ low motivation and external environmental influences. This study contributes to the development of a boarding-system-based religious character education model by emphasizing the integration of habituation, supervision, and exemplary practices as a holistic character-building ecosystem in Islamic higher education institutions.